1964
DOI: 10.1063/1.1725213
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Self-Broadened Widths of the Lines of the Hydrogen Bromide Fundamental Band

Abstract: The strengths and self-broadened half-widths of the lines of the fundamental band of HBr have been measured by a curve-of-growth method. The method uses a correction for two overlapping lines recently devised by Sakai. The squares of the electric dipole matrix elements, |M01(m)|2, for the lines have been calculated from the strengths. From the theory of Herman and Wallis and |M01(0)|2, the dipole moment derivative M1 is found to be 0.468×10—10 esu. From the slope at m = 0 of |M01(m)|2 the vibration—rotation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

1965
1965
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 17 publications
0
3
0
5
Order By: Relevance
“…20 The coefficient for the 6→5 transition was extrapolated by using a second power polynomial from the first five coefficients. Here the set of A coefficients previously reported for vibrational quantum numbers up to five is used.…”
Section: B Nascent Energy Distributionmentioning
confidence: 99%
“…20 The coefficient for the 6→5 transition was extrapolated by using a second power polynomial from the first five coefficients. Here the set of A coefficients previously reported for vibrational quantum numbers up to five is used.…”
Section: B Nascent Energy Distributionmentioning
confidence: 99%
“…Still, the interactioninduced effects involving heavier members of the HHal family received relatively little attention, so that the available experimental data on the line broadening and shifting in the IR spectra of HBr and HI remained sparse. The first measurement of the self-broadening coefficients determined using the curve-of-growth method applied to the isotopically unresolved fundamental band of HBr was published by Babrov [1]. Close values for the R 1 -branch lines were later obtained with a better resolution by Séoudi et al [2], who demonstrated that the H 79 Br and H 81 Br isotopomers yield, as expected, essentially identical results and also reported the line broadening coefficients for the HBr-CO 2 system.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the infrared spectra of HBr have been studied using grating spectrometers (1,(7)(8)(9)(10)(11)(12). The only laser-based highresolution measurements of HBr were performed in the high overtone bands (v ϭ 0 -6 to 0 -8; Ref.…”
Section: Introductionmentioning
confidence: 99%